Are the Hasmoneans legitimised as kings in 1 Maccabees? - Choi, Dongbin (2014)
Concerning the belief about continuation of the Davidic dynasty in the Second Temple Jewish literature, the present study seeks to understand how the belief may have been understood in 1 Maccabees. Specifically, it asks whether the Hasmoneans are legitimised as kings in the book, replacing the Davidic dynasty. Through examining relevant passages such as 2:57, 5:62, 14:25–49, and 14:41, it is argued that the author of 1 Maccabees does not present the Hasmoneans as legitimate kings. Instead, he preserves the traditional belief that the Davidic dynasty will continue.